1975
DOI: 10.1121/1.380685
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of voice amplitude by the monkey

Abstract: Old World monkeys (Macaca) were trained to vocalize at a steady rate in the laboratory by the use of operant conditioning techniques with food as a reinforcer. While the animals were vocalizing, they were subjected to one of two noise bands (200-500 Hz or 8-16 kHz) at different sound pressure levels (70, 80, and 90 dB SPL). Vocal amplitude was measured as a function of the SPL of the noise bands. The monkeys increased voice amplitude to the band of low-frequency noise but not to the high-frequency band. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 4 publications
5
74
0
Order By: Relevance
“…Most work on this Lombard effect used broadband stimuli to mask large portions of the animals' hearing range and therefore leaves open the question of whether specific frequency bands are important to elicit this effect. Only a few studies in birds (3, 7) and monkeys (17) found that masking noise yields the strongest Lombard effect when it covers the frequency range of the animals' calls. We show in horseshoe bats that call amplitudes exhibit robust shifts only when BFN masked the calls' dominant frequencies; even BFN extending up to 500 Hz below the dominant call frequencies did not have any significant effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work on this Lombard effect used broadband stimuli to mask large portions of the animals' hearing range and therefore leaves open the question of whether specific frequency bands are important to elicit this effect. Only a few studies in birds (3, 7) and monkeys (17) found that masking noise yields the strongest Lombard effect when it covers the frequency range of the animals' calls. We show in horseshoe bats that call amplitudes exhibit robust shifts only when BFN masked the calls' dominant frequencies; even BFN extending up to 500 Hz below the dominant call frequencies did not have any significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most efficient mechanisms is the socalled Lombard effect, i.e., the involuntary rise in call amplitude in response to masking ambient noise (1). This effect was first described in human communication a century ago (2) and has since been found in several species of birds (3)(4)(5)(6)(7)(8)(9)(10)(11) and various mammals (12)(13)(14)(15)(16)(17), including bats (18). In human speech, several vocal changes, such as a rise in fundamental frequency (19) or lengthening in word duration (20), are often accompanied with the Lombard effect; combined, these changes are referred to as Lombard speech (21).…”
mentioning
confidence: 99%
“…A third, most obvious, possible solution is simply to broadcast signals at a high enough amplitude to overcome ambient noise. Studies on different mammal, bird and frog species suggest that amplitude regulation constitutes a widespread form of plasticity in vocal performance (Sinnot et al 1975;Lopez et al 1988;Manabe et al 1998), but this solution is obviously only possible within physiological limits. To maintain the same active space in rainy conditions as in dry, tawny owls' calls would have to be emitted at 115.5 dB, an amplitude close to that of an aircraft taking off.…”
Section: Discussion (A) Estimation Of Active Spacementioning
confidence: 99%
“…Vocal behaviors like the Lombard response have been demonstrated to occur in a variety of birds [18,78] and mammals [54,109,125,135]. Echolocating bats maintain a very tight control over their voice amplitudes [42], and although the behavior has never been specifically categorized as a Lombard effect per se, background noise does cause a predictable increase in call intensity as well as other vocal adaptations [132].…”
Section: Audio-vocal Integration In Bats and Other Mammalsmentioning
confidence: 99%
“…To a large extent these similarities extend to other vertebrates, notably including songbirds [58], chorusing frogs [7], and even fish [35,67]. Ultimately the neural substrate for human speech will perhaps be distinguished by its more elaborate and sophisticated cortical circuitry [88], but surprisingly, many of the normal ways in which human speech responds to sensory feedback, such as in the case of the Lombard effect [76] or the response to pitch-shifted feedback [9,23], have been documented in a variety of other animals [54,113,116,135]. This fact illustrates the value of exploring the comparative neurophysiology of vocal motor patterning.…”
mentioning
confidence: 99%